BRAHMA VIDYÄ€ DALAM KITAB ÄªÅšÄ€ UPANIá¹¢AD (Studi Teologi Hindu) - Sura Adnyana, Putu Eka (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2019)
The book ÄªÅ›Ä Upaniá¹£ad is upanisad which is quite unique and important. ÄªÅ›Ä upaniá¹£ad is the shortest and smallest upaniá¹£ad of all 18 types of upaniá¹£ad, but is the most important upaniá¹£ad of all upaniá¹£ad books in Hinduism. ÄªÅ›Ä Upaniá¹£ad is always associated with Veda Åšruti, the Yajur Veda Putih (Åšukla Yajur Veda). ÄªÅ›Ä Upaniá¹£ad is in addition to the notion of ÄªÅ›Ä, as well as some of the teachings on which Hinduism is based. The book ÄªÅ›Ä Upaniá¹£ad described that the principles of the teachings contained in ÄªÅ›Ä Upaniá¹£ad, namely divinity, karma, the universe, vidyÄ and avidyÄ. God is called ÄªÅ›Ä. The absolute IÅ›Ä, and the Impersonal. The universe and all its contents are either soul or soulless, controlled by ÄªÅ›Ä. Therefore every living creature fights steadily with the karma and closer to God in his life. Furthermore, Brahma VidyÃ teachings contained in IÅ›Ä Upaniá¹£ad, namely: God almighty, God can not be thought, God is the source of all, God is everywhere, Ätman, sambhÅ«ti and asambhÅ«ti. God is called ÄªÅ›Ä, essentially Esa, the source of everything that exists in the universe and becomes the place of the return of all things. The one, while still in place, does not move, but his speed exceeds the mind, preceding the velocity of the Gods. God is unthinkable, supernatural, pervading everything, everywhere.